2018
DOI: 10.1002/admt.201800200
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Planar Microsupercapacitors: Recent Advances and Future Challenges

Abstract: The continuous development of integrated electronics such as maintenance‐free biosensors, remote and mobile environmental sensors, wearable personal electronics, nanorobotics etc. and their continued miniaturization has led to an increasing demand for miniaturized energy storage units. Microsupercapacitors with graphene electrodes hold great promise as miniaturized, integrated power sources thanks to their fast charge/discharge rates, superior power performance, and long cycling stability. In addition, planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 211 publications
(321 reference statements)
1
49
0
Order By: Relevance
“…[ 9,21–23 ] Among these materials, graphene has attracted great attention, thanks to its high surface‐to‐volume ratio, promising theoretical capacitance, and good intrinsic electrical and mechanical properties. [ 10,24–27 ] Several strategies have been developed to prepare the patterns for the graphene‐based electrodes of MSCs. The most common strategy is to use photolithography preparing interdigitated patterns of MSCs, but it suffers from its high cost and complex patterning processes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,21–23 ] Among these materials, graphene has attracted great attention, thanks to its high surface‐to‐volume ratio, promising theoretical capacitance, and good intrinsic electrical and mechanical properties. [ 10,24–27 ] Several strategies have been developed to prepare the patterns for the graphene‐based electrodes of MSCs. The most common strategy is to use photolithography preparing interdigitated patterns of MSCs, but it suffers from its high cost and complex patterning processes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] and supercapacitors (both conventional and small-scale devices). 2,3,5 As regards the former type of EES device, it is worth noting that current metal-ion batteries have reached their limits in terms of theoretical energy density, cycle life and charge/discharge rate, and so the development of a sustainable energy grid requires the implementation of new generations of batteries with enhanced features. In this context, metal-air (M-O2) batteries have arisen as an attractive alternative to conventional batteries due to their high theoretical energy density.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene can be used for the direct laying down of conductive or semi-conductive patterns on organic, flexible, transparent, wearable electronic devices, as well as being used in biomedical and nanomedicine applications, quantum devices, magnetic devices, super capacitors and small-scale, efficient energy storage devices, oil and petroleum, water treatment systems, biosensors, and even, in the possible construction of room temperature superconductive materials. [256][257][258][259] Recently, it has been shown that properties such as superconductivity or magnetism can be detected in a graphene bilayer in which the layers have been twisted with respect to each other at a so-called "magic" angle ( � 1.1 degrees). [260,261] Recently, flexible graphene based field effect transistors have been fabricated which are capable of monitoring slow brain waves (< 0.1 Hz) with high spatial resolution; this achievement could open new windows for the non-invasive wearable study of brain functions, including sleep, wakefulness, coma and anesthesia, allowing construction of more effective brain-machine interfaces and contributing to neuroscience studies.…”
Section: Applications Conclusion and Future Outlookmentioning
confidence: 99%